Electroplated telescopic retainers with zirconia primary crowns: 3-year results from a randomized clinical trial - Schwindling, Franz Sebastian; Lehmann, Franziska; Terebesi, Sophia; Corcodel, Nicoleta; Zenthöfer, Andreas; Rammelsberg, Peter; Stober, Thomas (Clinical oral investigations, 2017)
Objective:The objective of the study was to investigate the clinical outcome for electroplated telescopic removable dental prostheses (E-RDPs) with zirconia primary crowns.Materials and methodsSixty E-RDPs, with primary crowns manufactured from either cobalt-chromium alloy or zirconia, were fabricated for 56 participants. Electroplating was used to produce gold copings directly on the telescopic primary crowns. These copings were bonded intra-orally to the prosthesis framework. After 36 months, prosthesis survival and number of complications were assessed. Statistical analysis was performed by the use of Kaplan-Meier modeling and the log-rank test.ResultsSurvival of the E-RDPs, 96.4% after 3 years, was identical in both groups. The need for aftercare was high but not significantly different: technical complications were observed for 37% and 42.9% of the prostheses for the zirconia and cobalt-chromium alloy primary crowns, respectively. Fracture of composite veneer was the most frequent complication (59.1%). The incidence of fractured abutment teeth, decementation, and endodontic problems was 7.9% in the zirconia group and 14% in the control group. The majority of abutment-level complications were treated restoratively. A significant difference was found for maximum probing depth at the abutment teeth: In the zirconia group, it decreased by 0.2 mm, whereas it increased by 0.8 mm in the control group (p = 0.04).ConclusionsAfter 3 years of observation, survival of zirconia E-RDPs was favorable and comparable with that of established double-crown-retained prostheses. Further studies must clarify whether there are benefits of zirconia primary crowns for periodontal health.Clinical relevanceAlthough these results encourage the use of zirconia primary crowns, more research is necessary to reduce the number of complications observed for secondary telescopic crowns, for example, failure of the veneer.
First online: 11 February 2017
Gesehen am 20.06.2018